Bank efficiency in Southeast Asian countries: The impact of environmental variables - Mohd Khan, Shazida Jan (2014)
Since the 1997 financial crisis, the effected countries has implement huge changes by either accepting the financial support from International monetary funds (IMF) or taken an alternative step by stringent their capital policy.Since then, many researchers have taken the advantages by looking into the cause and fewer have look upon the impact of the policy in bank efficiency.This paper will implement a non-parametric analysis on the bank efficiency during the post crisis period of 1999 to 2005 and taken into consideration the implication of environmental variables.The early result suggested that the policy does significantly affected by the environmental variables in assuring the success of each policy changes and transformation as to regain the crisis region economic growth.